Entrapment of Brachial Artery and Median Nerve within the Brachialis Muscle – A Case Report - Vasanthakumar P.,; Nayak SB., (Department of Surgery, UKM Medical Centre, 2015)
Brachial artery and median nerve is the main neurovascular bundle of the arm. They have close relationship throughout the arm. Their entrapment may result in neurovascular symptoms in the distal part of the upper limb. We report a rare entrapment of these structures in the arm within the brachialis muscle. The brachial artery and median nerve entered the substance of brachialis at the junction of upper and middle thirds of the arm(after a course of about 8 cm). They came out through the tendon of brachialis in the cubital fossa.They coursed within the brachialis muscle for about 10 cm. There were no other variations in the arm. Knowledge of this entrapment may be useful for the orthopedic surgeons since there is a high chance of involvement of the artery and the nerve in the supracondylar fractures of the humerus.